Is gender studies absent in the Civic Education curriculum in higher education? - Febrianti, Nurul; Abdulkarim, Aim; Malihah, Elly; Fitriasari, Susan; Casmana, Asep Rudi (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This research aims to describe the position of gender studies in the curriculum of civic education study programs in universities. This research was conducted at several universities that have civic education study programs. The research used a qualitative descriptive approach and data collection techniques through interviews, observation, and documentation, while the data analysis technique used triangulation to obtain data validity. The results of the research found three things. First, the four universities that were the objects of this research developed curricula according to the provisions of the Ministry of Education and Culture. Second, there are explicitly no courses related to gender studies in the civic education curriculum at these universities. However, several lecturers try to bring gender issues into the learning process as a study case. Third, there are many challenges in integrating gender studies into the citizenship education curriculum, one of which is the expertise of civic education lecturers who cannot teach about gender. To overcome the challenges of integrating gender studies into the civic education curriculum, it is crucial to advocate for including gender studies to ensure comprehensive coverage of gender issues. This advocacy is a call to action for all involved in civic education. As well, developing strategies to integrate gender issues into existing courses through case studies, discussions, and projects can enrich the learning process.